Toward synthesis of novel thermoelectric organic semiconductors - Ritchie, John William (2018)
Thermoelectric devices provide an excellent method for the generation of electrical power from low grade waste heat from energy production, but the current best inorganic materials used for such devices are expensive and require dwindling resources. Organic semiconductors derived from tetracenes may therefore provide an excellent alternative. However existing synthetic methods are step and atom inefficient and as such would provide poor yield and cost efficiency in mass production, and there is a paucity of n-type organic materials compared to p-type, which limits device design. This report details attempts to develop rapid, general and scalable syntheses of tetracenes. A two-step process for the synthesis of substituted tetracenes via [3,3]-sigmatropic rearrangement cascade reaction from a series of bis-propargyl diols is disclosed. This method furnished a variety of tetracenes in up to quantitative yield from commercially available materials. Mechanistic insights into the novel anionic Chugaev cascade derived from DFT calculations are disclosed along with computed and experimentally derived HOMO-LUMO gaps. A brief analysis of the predicted electronic properties of some of the materials synthesised is then presented. In investigating bis-allenic cascades, an 8-membered ring was isolated in low yield. Mechanism of formation and the scope of the cascade which formed the carbocycle are briefly discussed. A second method toward the synthesis of tetracenes via an attempted nitrile cyclisation reaction is disclosed. The method suffered from the rapid oxidation of the derived peri-diaminotetracene, and attempts to temper the reactivity of the resultant tetracene were stymied by a difficulty in forcing a second ring closure, which proved resistant to further attempts to force cyclisation. A final method derived from an (E)-selective carbomagnesiation of 2-butyne-1,4-diol with various benzylmagnesium chlorides and trapping with iodine is disclosed. This allowed for a facile and high yielding Negishi-cross coupling with various benzylzinc halides to allow for various substitution patterns on the outermost aryl rings. A high yielding Stahl oxidation gave access to various dialdehydes in excellent to quantitative yields, allowing for a Lewis acid-mediated double closure with TiCl4. This step proved to be limited by the necessity of electron-donating groups to facilitate the double Bradsher closure, but allowed access to multiple substituted tetracenes.